Analysis of the Negative Impact of Gadgets on Elementary School Students - Nahdhiyatunisak Nahdhiyatunisak; Indra Susanti; Darsinah Darsinah; Wafroturrohmah Wafroturrohmah (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The development of digital technology has a significant impact on students' lives, particularly regarding the intensity of gadget usage at the elementary school level. This study aimed to analyze the negative impacts of gadget usage among students at SD Muhammadiyah 01 Kuripan Kidul, Pekalongan City, and to formulate coping strategies. Utilizing a descriptive qualitative approach, primary data were gathered through interviews, observations, and documentation, involving teachers, students, and parents as informants. Meanwhile, secondary data were obtained through document studies and scientific journals. All data were subsequently analyzed using an interactive model comprising data reduction, data display, and conclusion drawing. The results indicated that gadget usage among students at the school was relatively high and predominantly used for entertainment activities. The negative impacts identified by the researcher included decreased learning concentration, lack of social interaction, and behavioral changes such as lack of discipline and irritability. Furthermore, the recommended coping strategies focused on building synergy between parents and the school to limit and strictly monitor gadget screen time. Additionally, providing digital literacy education and alternative non-gadget activities could be implemented to foster a positive developmental environment for students at SD Muhammadiyah 01 Kuripan Kidul, Pekalongan City.